Exposure to organophosphate and polybrominated diphenyl ether flame retardants via indoor dust and childhood asthma. (23rd May 2015) - Canbaz, D.; van Velzen, M. J. M.; Hallner, E.; Zwinderman, A. H.; Wickman, M.; Leonards, P. E. G.; van Ree, R.; van Rijt, L. S.
Abstract: Although the ubiquitous detection of polybrominated diphenyl ether (PBDE) and organophosphate flame retardants (PFRs) in indoor dust has raised health concerns, only very few epidemiological studies have assessed their impact on human health. Inhalation of dust is one of the exposure routes of FRs, especially in children and can be hazardous for the respiratory health. Moreover, PFRs are structurally similar to organophosphate pesticides, which have been associated with allergic asthma. Thus, we investigated whether the concentrations of PFRs and PBDEs in indoor dust are associated with the development of childhood asthma. We selected 110 children who developed asthma at 4 or at 8 years old and 110 matched controls from a large prospective birth cohort (BAMSE – Barn, Allergy, Milieu Stockholm Epidemiology). We analyzed the concentrations of 7 PFRs and 21 PBDEs in dust collected around 2 months after birth from the mother's mattress. The abundance rank in dust was as follows: TBOEP⪢TPHP>mmp‐TMPP>EHDPHP TDCIPP>TCEP TCIPP BDE‐209⪢BDE‐99>BDE‐47>BDE‐153>BDE‐183>BDE‐100. There was no positive association between the FRs in mattress dust and the development of childhood asthma. In contrast, dust collected from mattresses of the mothers of children who would develop asthma contained significant lower levels of TPHP and mmp‐TMPP. This study provides data on a wide range of PFRs and PBDEs in dust samples and development of asthma in children.